Metodologi Penyusunan Kitab Hujjah Allah al-Balighah Karya Shah Wali Allah al-Dihlawi (1703-1762M) - Noraini Junoh; Ahmad Mushidi Mustapha; Abdul Manam Mohamad (USIM Press, 2024)
VOL. 27 (2022) Page (210-228)